Types of new world Oedionychini Chapuis, 1875 (Coleoptera, Chrysomelidae, Alticitae) deposited in the Naturhistoriska Riksmuseet, Stockholm - Roie, Martijn Van; Covelli, María Alejandra Álvarez (Zootaxa, 2026)
Type specimens of new world Oedionychini Chapuis, 1875 deposited in the collections of the Naturhistoriska Riksmuseet in Stockholm Sweden (NHRS) are examined and illustrated. Types from Carl Henrik Boheman, Julius Weise and Jan Bechyné were present. Lectotypes are designated for the following species: Asphaera purana Weise, 1921, Chloëphaga sparsata Bechyné, 1957, Homophoita superba Weise, 1921, Oedionychis decolorata Weise, 1921, Oedionychis delineata Weise, 1921, Oedionychis insignita Boheman, 1859, Oedionychis laetifica Boheman, 1859, Oedionychis lepida Boheman, 1859, Oedionychis nigrovittata Boheman, 1859, Oedionychis sternalis Weise, 1921, Omophoita gabriela Bechyné, 1957, Walterianella curvipes Bechyné, 1957, Walterianella malaisei Bechyné, 1957, Walterianella subordinata Bechyné, 1957. The holotype of Homophoita gloriosa Weise, 1921 is illustrated. The following new combinations are proposed: Walterianella decolorata (Weise, 1921) comb. nov., Walterianella delineata (Weise, 1921) comb. nov. and Callangaltica sternalis (Weise, 1921) comb. nov. The synonymy of Homophoita gloriosa Weise, 1921 with Omophoita angustolineata (Jacoby, 1905) is confirmed. We propose the new synonym of Walterianella subordinata Bechyné, 1957 with Walterianella delineata (Weise, 1921).